2016
DOI: 10.1038/nplants.2016.132
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying drought eliminates the expected benefits of elevated carbon dioxide for soybean

Abstract: Stimulation of C3 crop yield by rising concentrations of atmospheric carbon dioxide ([CO2]) is widely expected to counteract crop losses that are due to greater drought this century. But these expectations come from sparse field trials that have been biased towards mesic growth conditions. This eight-year study used precipitation manipulation and year-to-year variation in weather conditions at a unique open-air field facility to show that the stimulation of soybean yield by elevated [CO2] diminished to zero as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
205
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(243 citation statements)
references
References 54 publications
14
205
1
1
Order By: Relevance
“…An alternative route to minimize future heat-stressinduced yield losses could entail the introduction of greater chilling tolerance during germination and early seedling establishment, thereby facilitating earlier planting at lower soil temperatures to escape the more extreme heat stress that is currently coinciding with sensitive growth phases. Our findings are relevant for moderate-to high-yielding nonirrigated production environments, and we do not account for potential fertilization effects of increased CO 2 concentrations associated with global warming (33)(34)(35)(36)(37)(38). Future studies focusing on long-term climatic responses of crops under severe stress conditions would need to exercise appropriate measures to account for increasing atmospheric CO 2 and its interactions with other factors influencing yield response.…”
Section: Discussionmentioning
confidence: 97%
“…An alternative route to minimize future heat-stressinduced yield losses could entail the introduction of greater chilling tolerance during germination and early seedling establishment, thereby facilitating earlier planting at lower soil temperatures to escape the more extreme heat stress that is currently coinciding with sensitive growth phases. Our findings are relevant for moderate-to high-yielding nonirrigated production environments, and we do not account for potential fertilization effects of increased CO 2 concentrations associated with global warming (33)(34)(35)(36)(37)(38). Future studies focusing on long-term climatic responses of crops under severe stress conditions would need to exercise appropriate measures to account for increasing atmospheric CO 2 and its interactions with other factors influencing yield response.…”
Section: Discussionmentioning
confidence: 97%
“…A controlled-environment study of WUE i in soybean noted that g s , much more than A, dictates WUE i [14]. Another recent study showed that the expected benefits of rising atmospheric CO 2 concentration did not eventuate, owing to modified stomatal function and canopy energy balance [59]. One of very few direct comparisons of C 3 grasses (including cereals) with legumes, revealed that A was related to N per unit leaf area (N area ) for both groups, but that A was consistently greater in C 3 grasses than in legumes [60].…”
Section: Water Use Efficiency Of Grain Legume Versus Non-legume Cropsmentioning
confidence: 99%
“…Rising CO 2 may compensate for losses due to drought in some situations. However, a recent study – conducted over eight years under varying precipitation and with year-to-year variation in weather at a unique open-air field facility – revealed that stimulation of soybean yield by eCO 2 diminished to zero as drought intensified and eCO 2 interacted with drought to modify stomatal function and canopy energy balance (Gray et al, 2016). eCO 2 did not stimulate photosynthesis, biomass or grain yield, whereas the treatment combining eCO 2 and high temperature reduced grain yield in maize (Ruiz-Vera et al, 2015).…”
Section: Synthesismentioning
confidence: 99%